2021
DOI: 10.3389/fimmu.2020.619925
|View full text |Cite
|
Sign up to set email alerts
|

β2 Integrin Signaling Cascade in Neutrophils: More Than a Single Function

Abstract: Neutrophils are the most prevalent leukocytes in the human body. They have a pivotal role in the innate immune response against invading bacterial and fungal pathogens, while recent emerging evidence also demonstrates their role in cancer progression and anti-tumor responses. The efficient execution of many neutrophil effector responses requires the presence of β2 integrins, in particular CD11a/CD18 or CD11b/CD18 heterodimers. Although extensively studied at the molecular level, the exact signaling cascades do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 265 publications
(274 reference statements)
1
66
0
Order By: Relevance
“…How do PMo perceive that they have to increase the frequency of Lèvy-like walks for a more efficient search, especially for small targets, and how do they re-adapt their arsenal of adhesion and chemokine receptors to this type of movement? PMo show an amoeboid morphology when crawling in the slow phase of Lèvy-like walk suggestive of signals driven by b2 integrin interactions as shown in neutrophils (47,48). This is supported by the presence of a few Lèvy-like tracks in steadystate in the lung and kidney capillaries, territories with abundant endothelial CX3CL1, upregulator of b2 integrin affinity (3,19).…”
Section: Lèvy-like Crawlingmentioning
confidence: 72%
“…How do PMo perceive that they have to increase the frequency of Lèvy-like walks for a more efficient search, especially for small targets, and how do they re-adapt their arsenal of adhesion and chemokine receptors to this type of movement? PMo show an amoeboid morphology when crawling in the slow phase of Lèvy-like walk suggestive of signals driven by b2 integrin interactions as shown in neutrophils (47,48). This is supported by the presence of a few Lèvy-like tracks in steadystate in the lung and kidney capillaries, territories with abundant endothelial CX3CL1, upregulator of b2 integrin affinity (3,19).…”
Section: Lèvy-like Crawlingmentioning
confidence: 72%
“…A study in murine models demonstrated that cutaneous wounds heal faster in neutrophil-depleted mice compared with controls, concluding that excessive recruitment of neutrophils at the wound site may delay wound healing [ 61 ]. Macrophages can phagocyte neutrophils through β2 integrins after completion of DAMP clearance [ 54 , 62 ]. Furthermore, matricellular protein CCN1 also plays an important role in neutrophil clearance.…”
Section: Acute Wound Healingmentioning
confidence: 99%
“…CR3 is primarily expressed in leukocytes like neutrophils, monocytes, macrophages, and dendritic cells ( 9 ). Two main physiological roles have been described for CR3.…”
Section: Introductionmentioning
confidence: 99%
“…The events triggered by either signalling pathway generally recruit distinct effectors, for example, following engagement of the extracellular effector Mindin, CR3 outside-in signalling results in the activation of the MAPK pathway and translocation of NF-κb into the nucleus ( 16 ). In contrast, stimulation of G-protein coupled receptors results in the transition of CR3 from its low- affinity to its high-affinity state via an inside-out signalling pathway that includes the activation of phospholipases Cβ2 and Cβ3, and the calcium- and diacylglycerol-regulated guanine nucleotide exchange factor I (reviewed in ( 9 )). Some molecules can participate in both CR3 inside-out and outside-in signalling, including Rap1, RIAM, Talin, Kindlin and Syk ( 9, 1720 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation